Prognosis analysis of sacrococcygeal teratoma—compared with patient size - Park, Jueun; Ha, Suhyeon; Kwon, Hyunhee; Kim, Seong Chul; Namgoong, Jung-Man; Kim, Dae Yeon (Frontiers in Pediatrics, 2025)
IntroductionAdvancements in prenatal care have underscored the importance of understanding postnatal outcomes and prognosis in sacrococcygeal teratoma (SCT). However, giant SCTs continue to pose surgical challenges and are associated with increased morbidity and mortality. A clear, objective threshold for defining a “large” tumor relative to the patient's size remains undefined. This study aimed to establish objective tumor size indicators for predicting surgical outcomes and prognosis.MethodsData from 97 patients diagnosed with and surgically treated for SCT at Asan Medical Center from 2000 to 2021 was retrospectively reviewed. The tumor volume/birthweight ratio (VWR) and tumor length/height at birth ratio (LHR) were measured. Surgical outcomes and prognosis were evaluated based on these measures, including surgical complications, concomitant surgeries, long-term complications, and recurrence.ResultsAfter surgery, 38 patients experienced short-term complications, 18 required additional operations, 16 developed long-term complications, and 14 experienced tumor recurrence. Both VWR and LHR correlated with short and long-term complications, additional surgeries, and recurrence.DiscussionThe small patient population limited the determination of precise cut-off values; however, a significant difference was observed between groups stratified by the most predictive cut-off values. Both objective tumor size indicators were significantly associated with prognosis and surgical outcomes. Notably, both indicators exhibited comparable predictive capabilities without discrepancies.